2017
DOI: 10.7161/omuanajas.321115
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of relations between micro element availability and soil properties in Isparta-Atabey plain using principal component analysis

Abstract: ÖZETToprak oluĢum süreçlerine ve arazi kullanımına bağlı olarak ortaya çıkan toprak özellikleri topraklarda mikro element yarayıĢlılığı üzerine etki etmektedir. Bu çalıĢmada Isparta-Atabey ovasındaki 21 toprak serisinden alınan 70 toprak örneği incelenen 24 parametre ile toprakların yarayıĢlı mikro element konsantrasyonları arasındaki iliĢkiler tanımlayıcı istatistikler, Pearson korelasyonu ve temel bileĢen analiz yöntemleri kullanılarak incelenmiĢtir. Tanımlayıcı istatistik analizlerden çarpıklık katsayısının… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…These suggested that Fe, Zn, and Ni had higher traffic dependency than the the other elements. The availability of the elements however had larger dependency to traffic due to the added elements on to the indigenous occurrence has a tendency to be more mobile [35].…”
Section: Micronutrients Deposits-distance Relationshipsmentioning
confidence: 99%
“…These suggested that Fe, Zn, and Ni had higher traffic dependency than the the other elements. The availability of the elements however had larger dependency to traffic due to the added elements on to the indigenous occurrence has a tendency to be more mobile [35].…”
Section: Micronutrients Deposits-distance Relationshipsmentioning
confidence: 99%